2014
DOI: 10.18257/raccefyn.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waterlogging stress on the growth, development and symptomatology of cape gooseberry (Physalis peruviana L.) plants

Abstract: Waterlogging stress in cape gooseberry plants 393 Rev. Acad. Colomb. Cienc. Ex. Fis. Nat. 38(149) AbstractClimate change has altered normal rainfall cycles; causing the flooding of arable land and, thus, affecting agricultural production in Colombia. Two-month-old cape gooseberry plants, propagated by seeds, were subjected to different durations of continuous waterlogging in a greenhouse: 0, 2, 4, 6 and 8 days, with evaluations up to 50 days. The plants were placed in ditches covered with polyethylene and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 29 publications
(16 reference statements)
2
38
0
8
Order By: Relevance
“…Likewise, when plants were subjected to three different periods of waterlogging, the stem diameter was also lower in comparison to plants without stressful conditions (Table 2). Aldana et al (2014) also reported similar observations when a significant reduction in plant height and stem diameter was seen after subjecting cape gooseberry (another Solanaceae species) seedlings to eight-day waterlogging periods. Also, Florez-Velazco et al (2015) also evaluated the effect of the interaction between waterlogging vs. nutritional N status and found that a series of short periods of oxygen deficiency in the soil caused a decrease in the shoot length of lulo plants (another Solanaceae species) cultivated with two levels of N (10 vs. 150 mg N L -1 H2O), highlighting that the most significant reduction was observed in plants that were always nitrogen-deficient.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Likewise, when plants were subjected to three different periods of waterlogging, the stem diameter was also lower in comparison to plants without stressful conditions (Table 2). Aldana et al (2014) also reported similar observations when a significant reduction in plant height and stem diameter was seen after subjecting cape gooseberry (another Solanaceae species) seedlings to eight-day waterlogging periods. Also, Florez-Velazco et al (2015) also evaluated the effect of the interaction between waterlogging vs. nutritional N status and found that a series of short periods of oxygen deficiency in the soil caused a decrease in the shoot length of lulo plants (another Solanaceae species) cultivated with two levels of N (10 vs. 150 mg N L -1 H2O), highlighting that the most significant reduction was observed in plants that were always nitrogen-deficient.…”
Section: Resultssupporting
confidence: 59%
“…Malik et al (2002) also reported that even short periods (as short as 3 d) of waterlogging have important long-term effects on the growth of young wheat plants. On the other hand, Ezin et al (2010) and Aldana et al (2014) also observed that leaf growth and plant height varied according to the flooding duration in tomato and cape gooseberry plants, respectively.…”
Section: Waterlogging Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Hypoxic condition in shallow water table triggered alteration of plant morphology such as decreasing leaf area, reducing leaf expansion rate, and reducing leaf water content (Bradford and Hsiao, 1982;Ashraf, 2012;Aldana et al, 2014). Continuous observation of LA is useful for analyzing plant growth and development during stress condition.…”
Section: Rler As An Indicator Of Stress Due To Shallow Water Tablementioning
confidence: 99%